Adaptasi Struktur Histologi Insang Ikan pada Berbagai Kondisi Lingkungan: Kajian Literatur - Bismi Rahma Firna; Sandi Fransisco Pratama (Universitas Cokroaminoto Palopo, 2026)
Gills are vital organs in fish that function in respiration, osmoregulation, and ionic balance, making them highly sensitive to variations in environmental habitat conditions. Differences in water characteristics, such as water quality, dissolved oxygen, temperature, pH, and pollution levels, affect the structure and histological condition of the gills. This article aims to critically review and synthesize the structure and histological adaptations of fish gills in response to differences in habitat conditions through a literature review approach of reputable national and international publications. The results of the synthesis indicate that variations in environmental conditions trigger distinctive histological changes, including epithelial hyperplasia and hypertrophy, increased mucus and chloride cells, secondary lamella fusion, edema, and changes in vascularization, which reflect physiological adaptation mechanisms as well as early indicators of structural disorders due to environmental stress. Thus, the histological characteristics of fish gills have high potential to be used as biological biomarkers in assessing the quality of aquatic habitats and the health of aquatic ecosystems, as well as as a basis for the development of sustainable environmental biomonitoring.